GENEALOGY OF THE THOUGHT OF MAQĀṢID Al-SYĀṬIBῙ: AN INTERTEXT STUDY OF THE BOOK AL-MUWĀFAQĀT - Akhmad Sulaiman (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This article examines the genealogy of al-Syāṭibī’s maqāṣid thought in al-Muwāfaqāt, focusing on its intertextual roots and later influence in contemporary Islamic legal thought. Using qualitative library research and intertextual analysis, it reads al-Muwāfaqāt not as an isolated text, but as part of a broader network of uṣūl al-fiqh traditions before and after al-Syāṭibī. The study argues that al-Syāṭibī’s maqāṣid theory was not entirely new, but represented a systematic development and epistemological reconstruction of earlier ideas, especially al-Ghazālī’s conception of maṣlaḥah mursalah. Al-Syāṭibī’s major contribution lies in transforming maṣlaḥah mursalah from a subsidiary legal proof into a foundational principle of Islamic legal reasoning. The article also shows that the Mālikī intellectual milieu of Granada, along with rational elements introduced through Mu‘tazilite theology and philosophy, contributed to the formation of his thought. After a long period of dormancy, al-Syāṭibī’s maqāṣid thought was revived through the publication of al-Muwāfaqāt in Tunisia and later developed by Ibn ‘Āshūr, contemporary uṣūl scholars, and Qur’anic hermeneutical thinkers such as Abdullah Saeed.